The uptake of [18F]-fluorodeoxyglucose by the renal allograft correlates with the acute Banff scores of cortex inflammation but not with the 1-year graft outcomes - Fank, Hélène; Weekers, Laurent; Lovinfosse, Pierre; Pottel, Hans; Seidel, Laurence; Jadoul, Alexandre; Bouquegneau, Antoine; Bonvoisin, Catherine; Bovy, Christophe; Grosch, Stephanie; Erpicum, Pauline; Hustinx, Roland; et al. (Frontiers in Transplantation, 2023)
Introduction [18F]FDG PET/CT noninvasively disproves acute kidney allograft rejection (AR) in kidney transplant recipients (KTRs) with suspected AR. However, the correlation of biopsy-based Banff vs. PET/CT-based scores of acute inflammation remains unknown, as does the prognostic performance of [18F]FDG PET/CT at one year post suspected AR. Methods From 2012 to 2019, 114 [18F]FDG-PET/CTs were prospectively performed in 105 adult KTRs who underwent per cause transplant biopsies. Ordinal logistic regression assessed the correlation between the extent of histological inflammation and the mean standardized [18F]FDG uptake values (mSUVmean). Functional outcomes of kidney allografts were evaluated at one year post per cause biopsy and correlated to mSUVmean. Results A significant correlation between mSUVmean and acute Banff score was found, with an adjusted R2 of 0.25. The mSUVmean was significantly different between subgroups of “total i”, with 2.30 ± 0.71 in score 3 vs. 1.68 ± 0.24 in score 0. Neither the function nor the survival of the graft at one year was statistically related to mSUVmean. Discussion [18F]FDG-PET/CT may help noninvasively assess the severity of kidney allograft inflammation in KTRs with suspected AR, but it does not predict graft outcomes at one year.